2012
DOI: 10.2169/internalmedicine.51.6094
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Control of Cardiovascular Risk Factors in Patients with Type 2 Diabetes -A Cross-Sectional Study

Abstract: Objective Trends in diabetes and cardiovascular mortality rates are considerably different between women and men; this can be partially explained by differences in diabetes control. The aim of this cross-sectional study was to assess whether sex differences exist in effective control of cardiovascular risk factors among persons with type 2 diabetes treated at the Vuk Vrhovac University Clinic in 2008. Materials and MethodsWe performed a cross-sectional analysis including 8,775 patients who attended the clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
6
17
0
1
Order By: Relevance
“…However, a number of recent studies that focused on gender differences [25-30] found that female patients with diabetes had a worse cardiovascular risk profile and were less controlled compared to their male counterparts. Our study confirmed these results in part; women in DIAB-CORE had higher total cholesterol values than men.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent studies that focused on gender differences [25-30] found that female patients with diabetes had a worse cardiovascular risk profile and were less controlled compared to their male counterparts. Our study confirmed these results in part; women in DIAB-CORE had higher total cholesterol values than men.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that diabetic women compared with non-diabetic women may have a more severe degree of CVD risk factor abnormalities than their male counterparts or the impact of these factors on CVD mortality may be greater in diabetic women than in men (20). In particular, several parameters, such as BMI, TC, LDLC, apolipoprotein B and TG levels and small LDL particles (most of them related to insulin resistance), seem to provide stronger prediction of diabetes-related CHD events in women than in men (29,30,31,32). Furthermore, differences exist with respect to coagulation factors (higher levels of factor VIII), increased blood viscosity, endothelial dysfunction (higher levels of tissue plasminogen activator) and inflammation, as indicated by higher white cell blood count (28), a CHD and an allcause mortality prognostic factor (33).…”
Section: Differences In Factors That Might Contribute To Sex Differenmentioning
confidence: 99%
“…1,[8][9][10] A review of the literature shows that men with T2DM often have better cardiovascular risk profiles and outcomes compared with women with T2DM. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Women with diabetes have a three-to fivefold higher risk of developing CVD, and men have a two-to threefold higher risk compared with their respective counterparts without diabetes. 2,10,11,[14][15][16][17][25][26][27] Regardless, both men and women living with diabetes can lower their risk of CVD by adjusting modifiable factors below specific thresholds such as glycosylated hemoglobin A1c (HbA1c) level <7%, blood pressure (BP) <130/80 mm Hg, and low-density lipoprotein (LDL) cholesterol level <100 mg/dL.…”
Section: Introductionmentioning
confidence: 99%
“…23 More evidence is needed to determine why gender differences in CVD risk factor control continue, and some postulate that this difference may be due to variances in clinical practice. In a systematic review of gender differences related to treatment of CVD, there was a 20% significant difference in cardiovascular-related outcomes by gender 31 such that women demonstrated more adverse outcomes in the majority of the studies reviewed.…”
mentioning
confidence: 99%